2021
DOI: 10.1177/10541373211000175
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effectiveness of Acceptance and Commitment Therapy for Managing Grief Experienced by Bereaved Spouses or Partners of Adults Who Had Received Palliative Care

Abstract: This systematic review investigated the effectiveness of Acceptance and Commitment Therapy (ACT) for managing grief experienced by bereaved spouses or partners of adults who had received palliative care. Systematic searches were undertaken on seven bibliographic databases and grey literature was also searched. The review was informed by the use of the PICO framework and PRISMA-P guidelines. Initially 30 relevant papers were identified, but only two international studies met the criteria for inclusion. One was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…A past study suggested that new parents who report partner and peer support perceive more control over health behaviors because of these reciprocal supports [76]. Higher perceived control in the general population is consistently correlated with decreased symptoms of depression and anxiety, which may be a result of mechanistic pathways related to adaptive coping behaviors, such as mindfulness [77][78][79][80]. MBIs are designed to integrate intention and awareness into everyday life [81][82][83].…”
Section: Discussionmentioning
confidence: 99%
“…A past study suggested that new parents who report partner and peer support perceive more control over health behaviors because of these reciprocal supports [76]. Higher perceived control in the general population is consistently correlated with decreased symptoms of depression and anxiety, which may be a result of mechanistic pathways related to adaptive coping behaviors, such as mindfulness [77][78][79][80]. MBIs are designed to integrate intention and awareness into everyday life [81][82][83].…”
Section: Discussionmentioning
confidence: 99%
“…The dearth of evidence on Acceptance and Commitment Therapy for bereavement was also recently noted in a systematic review on managing grief, which only identified two studies. 40 Future research is needed to explore the acceptability and value of Acceptance and Commitment Therapy for people who have been bereaved. Similarly, only two studies involving palliative care staff were identified, 45,56 however given the effectiveness of Acceptance and Commitment Therapy in promoting wellbeing in other occupational settings, 37 further research examining Acceptance and Commitment Therapy for palliative care staff wellbeing is warranted.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…28 However, despite the emerging evidence base for the effectiveness of Acceptance and Commitment Therapy across a range of populations and contexts, we identified only three reviews focused specifically on advanced progressive illness or bereavement. [38][39][40] Two of these reviews concluded that Acceptance and Commitment Therapy may be beneficial in improving quality of life and alleviating symptoms of anxiety and distress amongst patients with advanced cancer 38,39 However, both reviews excluded studies of people with advanced illnesses other than cancer, and considered evidence based on RCTs or quasi-experimental studies only. 38 Neither review sought to explore the potential value of Acceptance and Commitment Therapy for caregivers or staff involved in the care of people with advanced progressive illness.…”
Section: Introductionmentioning
confidence: 99%
“…A inflexibilidade psicológica, especialmente a esquiva experiencial tem se mostrado como um preditor da maior presença de luto prolongado, enquanto os valores e ações com compromisso reduzem o luto prolongado (Davis et al, 2015;Eisma et al, 2015). Uma revisão sistemática sobre o uso da ACT para cuidadores enlutados no contexto de CP encontrou evidências de benefícios, especialmente em relação à aceitação de emoções dolorosas advindas desse momento (Jones, Methley, Boyle, Garcia, & Vseteckova, 2021). Ainda, a flexibilidade psicológica teve um papel protetivo contra psicopatologias nos enlutados, o que pode prevenir o luto prolongado ou traumático.…”
Section: Act Para Cuidadores Informais No Contexto De Cpunclassified